Blood flow restriction is not useful as soccer competition recovery in youth male national-level soccer players: a crossover randomised controlled trial - Castilla-López, C.; Romero-Franco, N. (Sports, 2023)
In soccer, blood flow restriction (BFR) is used to optimise between-match recovery. However, the benefits are unclear. This study evaluated the effects of BFR as a recovery strategy after a competition on countermovement jump (CMJ) height, rating of perceived exertion (RPE) and the wellness of soccer players. Forty national-level soccer players were allocated into two conditions: BFR (an active recovery session wearing a BFR device, 24 h after a competition) or NoBFR (the same recovery without BFR). CMJ, RPE and wellness were evaluated the day (CMJ and RPE) or the morning (wellness) before the competition; just after the competition (CMJ and RPE); and 24, 48 (wellness) and 72 h later. After 4 weeks, the players changed conditions. All players showed impaired CMJ (p = 0.013), RPE (p < 0.001) and wellness (p < 0.001) after the match compared with the baseline. The CMJ returned to the baseline 24 h later and wellness returned 48 h later. Only in the BFR condition did the RPE remain impaired 24 h after the match, which was also the moment after finishing the BFR recovery session (p < 0.001). BFR during active recovery does not provide any additional benefits compared with traditional exercise modalities to recover CMJ, RPE and wellness in youth national-level soccer players. BFR could even induce an immediate higher RPE.